An Inclusive Approach to Hands-on STEM Programs in Underserved Secondary Schools: An Epistemological STEAM Model - Alade, Martha Omoekpen; Sadiq, Fatai; Ikpotokin, Festus (My University, 2023)
Underserved schools globally do not usually have sufficient resources and requisite models to run inclusive and sustainable hands-on STEM programs. This often lead to exclusion of more students from opportunities in STEM, especially those with disabilities and learning difficulties. The marginalization of disadvantaged learners and exclusion of majority of students in resource-poor schools creates an internal STEM gap. Some schools having resources but lacking skilled instructors also face the same challenges. After more than a decade of casual observations, these problems have remained consistent, persistent and widespread; especially in developing countries. This mixed and longitudinal study therefore proposes an inclusive framework to address these inequities in STEM. Our model comprises seven components, after inductive analysis of empirical observations. A survey of 214 participants comprising 36 teachers and 178 students, who have participated in hands-on STEM programs was analyzed using simple statistical method to evaluate their perceptions on our hypothesized propositions. Our findings reveal that teachers' and students' responses validate our proposed framework; which informs the development of our Epistemological STEAM Model. This framework would serve as an effective guide for underserved secondary schools to implement sustainable hands-on programs with limited resources. It would also help policy makers enforce inclusion in the selection of students who participate annually in sponsored STEM programs and competitions; as well as drive optimal utilization of public STEM infrastructures.
Keywords: Secondary Schools; STEAM Model; Epistemological Model